Neo-Victorianism - Heilmann, Ann. author. aut Link
XII, 323 p.
Keywords: This field-defining book offers an interpretation of the recent figurations of neo-Victorianism published over the last ten years. Using a range of critical and cultural viewpoints, it highlights the problematic nature of this 'new' genre and its relationship to re-interpretative critical perspectives on the nineteenth century.